Dynamic Changes of the Gut Microbiota in Preterm Infants With Different Gestational Age - Jia, Qiong; Yu, Xue; Chang, Yanmei; You, Yanxia; Chen, Zekun; Wang, Ying; Liu, Bin; Chen, Lijun; Ma, Defu; Xing, Yan; Tong, Xiaomei (Frontiers in Microbiology, 2022)
The gut microbiota plays a key role in the pathogenesis of diseases affecting preterm infants and gestational age is one of the important factors which affect the gut microbiota of infants. To determine the characteristics of the gut microbiota in preterm infants of different gestational ages from birth to 1 year after birth, we collected 622 fecal samples from neonates of different gestational ages at different time points after birth. According to the gestational ages, the samples were divided into four groups, extremely preterm, very preterm, moderate to late preterm, and term group. Meconium and fecal samples at day 14, 28, 120, and 365 after birth were collected. 16S rRNA sequencing was performed and the composition and structure of the gut microbiota in preterm infants of different gestational age was compared with that of term infants. In our study, alpha diversity of meconium in extremely preterm group was higher than very preterm group, moderate to late preterm group and term group and alpha diversity of meconium in preterm group was decreased with increasing of gestational age. At day 14 to day 120 after birth, alpha diversity of term and moderate to late preterm group were significantly higher than other two preterm groups. However, moderate to late preterm group owned the highest alpha diversity which was higher than term group at day 365 after birth. Besides, the results shown the duration of opportunistic pathogen such as Klebsiella and Enterococcus which dominant colonization was different in different gestational age groups. As well as the probiotics, such as Bifidobacterium, which abundance enriched at different time point in different gestational age groups. We profiled the features of dynamic changes of gut microbiome from different gestational ages infants. The results of our research provide new insights for individualized interventions of specific microbes of preterm infants with different gestational ages at different time points after birth.